Antibiotic consumption in Turkish hospitals; a multi-centre point prevalence study. (2nd January 2017) - Guclu, Ertugrul; Ogutlu, Aziz; Karabay, Oguz; Demirdal, Tuna; Erayman, Ibrahim; Hosoglu, Salih; Turhan, Vedat; Erol, Serpil; Oztoprak, Nefise; Batirel, Ayse; Altay, Fatma Aybala; Kaya, Gulsum; et al.
Abstract : This multi-centre study aimed to determine the antibiotic consumption in Turkish hospitals by point prevalence. Antibiotic consumption of 14 centres was determined using the DDD method. Among hospitalized patients, 44.8% were using antibiotics and the total antibiotic consumption was 674.5 DDD/1000 patient-days (DPD). 189.6 (28%) DPD of the antibiotic consumption was restricted while 484.9 (72%) DPD was unrestricted. Carbapenems (24%) and beta lactam/beta lactamase inhibitors (ampicillin-sulbactam or amoxicillin-clavulanate; 22%) were the most commonly used restricted and unrestricted antibiotics. Antibiotics were most commonly used in intensive care units (1307.7 DPD). Almost half of the hospitalized patients in our hospitals were using at least one antibiotic. Moreover, among these antibiotics, the most commonly used ones were carbapenems, quinolones and cephalosporins, which are known to cause collateral damage. We think that antibiotic resistance, which is seen at considerably high rates in our hospitals, is associated with this level of consumption.